Are Segmenting, Targeting, and Positioning Necessary for Strategic Marketing? - Amira, Hisan; Fitriasari, Nikma (Jurnal Kedokteran Brawijaya)
Changes in the hospital environment have led to an increasingly competitive market. Marketing strategies are vital ingredients to offer more creative, innovative, and valuable products to customers to compete with other hospitals. Hyperbaric Oxygen Teraphy (HBOT) installation is one of the superrior service atÂ  Paru Hospital Jember which have a low number of visit for the last three years. Segmenting, targeting, and positioning (STP) strategies will help to identify the most profitable market, which can be used to create the right connection to customers. This research aimed to arrange STP strategies as a base for the hospital strategic marketing plan at Hyperbaric Oxygen Therapy (HBOT) installation of Paru Hospital Jember. This research was a descriptive study. The root of the problems was identified using the urgency, seriousness and growth (USG) method and followed by identifying the problem solutions with the capability, accessible, readiness and leverage (CARL) method before finding the solutions. The results of this study show that the five geographic segmentation areas of the target market are Jember, Probolinggo, Lumajang, Bondowoso, and Banyuwangi. The targets are patients older than five years old, middle-high economic class people, patients with diabetic foot, Buerger's disease, and sudden deafness. The new tagline â€œTabikâ€ stands for â€œInstalasi Hiperbarik,â€ and the new motto â€œJadikan hidup lebih baik bersama Tabikâ€ is a positioning made for STP strategies. Ten-year projection showed a gap visit number as many as 1.958 patients with STP as a strategic marketing plan in HBOT Installation Paru Hospital Jember. The implementation of the marketing mix is one tool to reach the gap. Implementation of the promotion is the first element of the marketing mix to complete to reach number of visits gap.Â